2016
DOI: 10.3126/banko.v23i2.15462
|View full text |Cite
|
Sign up to set email alerts
|

Influence of climate on radial growth of Abies pindrow in Western Nepal Himalaya

Abstract: This study aims to understand the influence of climate on radial growth of Abies pindrow growing in the plateau of mixed forest in Khaptad National Park in Western Nepal Himalaya. Based on the dated tree-ring samples, 362-year long tree-ring width chronology was developed dating back to 1650. The studied taxa of this region was found to have dendroclimatic potentiality that was evident from the chronology statistics calculated. The tree-ring chronology was correlated with climate (temperature and precipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…The correlation coefficient within tree was high and similar at three sites (~ 0.50-0.63) but comparatively lower (~ 0.31) at the 3100 m elevation site. Similar correlation coefficients have been reported in other tree ring studies from the Himalaya region (Sano et al, 2005;Bhuju et al, 2010;Chhetri and Thapa;Gaire et al, 2011;Dawadi et al, 2013;Thapa et al, 2013). The Expressed Population Signal (EPS) of the chronologies of all four sites exceeded the suggested threshold limit of 0.85%, indicating that the chronologies developed from the available sample size represented the site chronologies of the respective elevations well (Wigley et al, 1984).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The correlation coefficient within tree was high and similar at three sites (~ 0.50-0.63) but comparatively lower (~ 0.31) at the 3100 m elevation site. Similar correlation coefficients have been reported in other tree ring studies from the Himalaya region (Sano et al, 2005;Bhuju et al, 2010;Chhetri and Thapa;Gaire et al, 2011;Dawadi et al, 2013;Thapa et al, 2013). The Expressed Population Signal (EPS) of the chronologies of all four sites exceeded the suggested threshold limit of 0.85%, indicating that the chronologies developed from the available sample size represented the site chronologies of the respective elevations well (Wigley et al, 1984).…”
Section: Resultssupporting
confidence: 86%
“…The number of dendroclimatic studies in Nepal Himalaya is increasing at a considerable pace (Cook et al, 2003;Sano et al, 2005;Bhuju et al, 2010;Chhetri and Thapa, 2010;Gaire et al, 2011;Dawadi et al, 2013;Thapa et al, 2013). However, so far no studies have focused on examining climate-tree growth relationships along elevation gradients in the Nepal Himalaya despite the marked gradients characterizing this region.…”
mentioning
confidence: 99%
“…Additionally, Thapa et al . (, ) have demonstrated a clear negative temperature and a positive precipitation signal in Abies during the pre‐monsoon period (March–May) as well as a strong inverse relationship between Picea TRW and spring temperature (March–May) in the western Nepalese Himalayas. Exceptionally, the Abies chronology reported here showed a significant positive response to January temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of moisture availability is confirmed by a previous study from the western Himalayas, India, where a high significant positive correlation with the Palmer Drought Severity Index was also revealed (Ram, 2012;Ram and Borgaonkar, 2013). Additionally, Thapa et al (2013Thapa et al ( , 2015 have demonstrated a clear negative temperature and a positive precipitation signal in Abies during the pre-monsoon period (March-May) as well as a strong inverse relationship between Picea TRW and spring temperature (March-May) in the western Nepalese Himalayas. Exceptionally, the Abies chronology reported here showed a significant positive response to January temperature.…”
Section: Dendroclimatic Signalsmentioning
confidence: 96%
“…Our ring-width chronology indicates negative correlations with the March-May average temperature and positive relations with March rainfall, which is also considered as the spring season in Nepal. Most of the conifers in the high Himalaya show similar responses to the temperatures in the early growth period [15,19,23,24,26,55,56]. In the high Himalaya, broad-leaved species (Betula utilis D.Don) also show a negative response with spring temperature and a positive relationship with precipitation [53,57,58].…”
Section: Characteristics Of the Timang T Dumosa Chronologymentioning
confidence: 99%